IN SILICO STUDY OF PHYSALIS ANGULATA COMPOUNDS AS POTENTIAL THERAPEUTICS FOR ECZEMATIC SKIN DISEASES - Yan Martin Witantra (PT. Radja Intercontinental Publishing, 2026)
Eczema, a broad term encompassing a number of chronic inflammatory skin disorders, is typically characterized by symptoms such as redness (erythema), itching (pruritus), dryness, thickening of the skin due to repeated scratching (lichenification), and the possible appearance of fluid (exudation) or small blisters (vesicles). IL-4 and IL-13 activate the JAK-STAT pathway through the IL-4Rα and IL-13Rα1 receptors, which promotes STAT6 activation and the inflammatory response in atopic dermatitis, thus providing the basis for the use of upadacitinib as a selective JAK1 inhibitor that is effective in alleviating the symptoms of the disease. The aim of this study was to explore potential therapeutic pathways, with particular attention to compounds present in Physalis angulata , including the withanolide group such as withangulain B, physagulin C, and withanolide, which is one of 41 groups of compounds that have been identified in Physalis angulata . In addition, this study also evaluated the control drug upadacitinib, which is designed to target the IL-4Rα and IL-13Rα1 receptors, which play a key role in the type 2 (Th2) immune response. The study utilized several computational techniques, including data mining, biological activity analysis, ADMET (Absorption, Distribution, Metabolism, Excretion, and Toxicity) profiling, molecular mapping, and in silico studies. The results showed that the binding energies of the ligands (Physagulin C and Withangulatin B) with the IL-4Rα receptor were -12.6 kcal/mol and -12.7 kcal/mol, respectively. Similarly, Withanolide and Withagulatin B were identified as the top candidate compounds for the IL-13Rα1 receptor, with binding energies of -11.5 and -11.5 kcal/mol, respectively. The interactions above are the most beneficial for the development of eczematic disease therapy. The overall results of this study demonstrate great potential, indicating that the withanolide compounds, physagulin c, and withangulatin B derived from Physalis angulata offer an alternative pathway in targeting immune cells (Th2) through JAK-STAT activation and STAT6 translocation to the nucleus. Therefore, this study opens up opportunities for the development of innovative therapies in the treatment of eczematic diseases.